Thiol–Ene Click Reaction as a Facile and General Approach for Surface Functionalization of Colloidal Nanocrystals. Issue 36 (10th August 2017) - Liu, Bin; Deng, Xiaoran; Xie, Zhongxi; Cheng, Ziyong; Yang, Piaoping; Lin, Jun
Abstract : Oleic acid (OA) and/or oleylamine (OAm) are generally used as the surface ligands for stabilization of inorganic nanocrystals (NCs). The hydrophobic and inert surface of the NCs limits their applications such as in biomedical areas. Hence, surface modifications are essential in many physical and chemical processes. Here, a facile and versatile strategy is reported for the modification of NCs by ultraviolet‐induced thiol–ene chemistry, in which thiol‐terminated poly(ethylene glycol) (HSPEG) and its derivatives can react directly with double bonds in OA/OAm ligands to form covalent linking within one step. Through this strategy, various hydrophobic NCs with different compositions and morphologies are able to be transferred into water combining with functionalization of active groups. As a proof‐of‐concept, this strategy is successfully used to construct a sensor for detecting avidin based on upconverting luminescence analysis. Therefore, this strategy provides a new tool for designing and tuning the surface properties of NCs for different applications. Abstract : The modification of nanocrystals (NCs) by ultraviolet‐induced thiol–ene chemistry through a facile and versatile strategy is reported, in which thiol‐terminated poly(ethylene glycol) (HSPEG) and its derivatives can react directly with double bonds in oleic acid/oleylamine ligands to form covalent linking within one step. This strategy provides a new tool for designing and tuning the surface properties of NCs.